ПУТИ ДАЛЬНЕЙШЕГО СОВЕРШЕНСТВОВАНИЯ ПАРЛАМЕНТАРИЗМА В РЕСПУБЛИКЕ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the questions of further potential parliamentarianism enhancement and development in the Republic of Kazakhstan. Theplace and a role of a voting right, the legislation on political parties in parliamentarianism development in the country are shown. Questions ofcooperation coordination of its Kazakhstan Parliament Chambers between themselves, together with other state authorities are reviewed.